Altered brain network centrality in patients with cervical spondylotic myelopathy: insights from resting-state fMRI - Wu, Kaifu; Zheng, Hui; Jiang, Yan; Zhang, Shutong; Wang, Xiang (Frontiers in Neurology, 2025)
ObjectiveTo investigate the characteristics of brain network centrality in patients with cervical spondylotic myelopathy (CSM) by using degree centrality (DC) based on resting-state functional magnetic resonance imaging.MethodsWe recruited 20 patients with CSM, along with 20 healthy controls (HC) who were matched in terms of age, gender, and educational background. The DC method was utilized to evaluate the changed spontaneous brain activities. The relationships between the DC values of different brain regions and the clinical features were analyzed by means of Pearson correlation analysis.ResultsCompared with HC, CSM group showed decreased DC values in the left medial frontal gyrus, middle temporal gyrus and angular gyrus, and increased DC values were found in the left middle occipital gyrus, right supplementary motor area (p < 0.05). There was no significant correlation between DC values of abnormal region and clinical function score of CSM patients (p > 0.05).ConclusionCSM patients have abnormal DC distribution in the whole-brain functional networks, which might be related to cortical reorganization after chronic spinal cord injury.